The influences of adrenaline dosing frequency and dosage on outcomes of adult in-hospital cardiac arrest: A retrospective cohort study. (June 2016) - Wang, Chih-Hung; Huang, Chien-Hua; Chang, Wei-Tien; Tsai, Min-Shan; Yu, Ping-Hsun; Wu, Yen-Wen; Hung, Kuan-Yu; Chen, Wen-Jone
Abstract: Aim: To investigate the influence of dosing frequency and dosage of adrenaline on outcomes of cardiopulmonary resuscitation (CPR). Methods: We conducted a retrospective observational study in a single medical centre and included adult patients who had suffered an in-hospital cardiac arrest between 2006 and 2012. We used multivariable logistic regression analysis to evaluate the associations between independent variables and outcomes. Adrenaline average dosing frequency was calculated as the total dosage of adrenaline administered during CPR divided by the duration of CPR. Body weight (BW) was analysed as an interaction term to investigate the effect of adrenaline dosage on outcomes. Favourable neurological outcome was defined as a score of 1 or 2 on the Cerebral Performance Category scale at hospital discharge. Results: We included 896 patients in the analysis. After adjusting for multiple confounding factors, including CPR duration, the results indicated that higher adrenaline dosing frequency was associated with lower rates of survival (odds ratio (OR): 0.05, 95% confidence interval (CI): 0.01–0.23) and favourable neurological outcome at hospital discharge (OR: 0.02, 95% CI: 0.002–0.16). A significant interaction was noted between total adrenaline dosage and BW, which indicated that, with the same adrenaline dosage, the outcomes for patients with BW ≥ 82.5 kg would be worse than those for patients with lower BW. Conclusion: Higher adrenaline average dosing frequency may be associated with worse outcomes after CPR. Besides, according to current recommendations, patients with BW above 82.5 kg may not receive adequate dose of adrenaline.